KEBIJAKAN KOMITMEN ORGANISASIONAL YANG KUAT AKAN MENINGKATKAN KINERJA PERAWAT - Lukman Indra Irawan; Sih Darmi Astuti (Pusat Riset dan Inovasi Nasional, 2021)
This study aims to determine whether Leadership, Work Discipline, Organizational Commitment and Its Impact on the Performance of Nurse Rsud Wongsonegoro in Semarang and analyze the most dominant factors in influencing the performance of Rsud Wongsonegoro nurses in Semarang. In this study the study population refers to nurses Wongsonegoro Hospital Semarang. Samples taken as many as 67 respondents using purposive sampling technique. The equation model is processed using SPSS for Windows Version 20. The data testing techniques used in this study include the validity test, reliability test with Cronbach Alpha, classic assumption test, multicollinearity test and heteroscedasticity test, normality test, multiple linear regression analysis, t, F test and coefficient of determination test. Based on the results of the study, leadership variables, work discipline and organizational commitment have a positive and significant effect on nurse performance.